2022
DOI: 10.1007/s10616-022-00566-8
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular epimorphin impairs expression and processing of profilaggrin in HaCaT keratinocytes

Abstract: The expression and processing of laggrin, a lament-associated protein in the skin epidermis, is closely associated with keratinocyte corni cation. The large precursor pro laggrin (Pro-FLG) is initially detected at the granular layer in keratohyalin granules, subsequently processed into ten to twelve laggrin monomers (mFLGs) for keratin assembly, and ultimately degraded into smaller peptides that behave as natural moisturizing factor (NMF) at the outermost epidermis. We previously reported that a t-SNARE protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…1 ). Furthermore, it has been reported that FLG is very unstable in HaCaT cells, which express caspase14 to digest FLG into small peptides known as natural moisturizing factors (NMFs) 12 .
Figure 2 The regulation of mesotrypsin expression in HaCaT cells is governed by a protein elimination system.
…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1 ). Furthermore, it has been reported that FLG is very unstable in HaCaT cells, which express caspase14 to digest FLG into small peptides known as natural moisturizing factors (NMFs) 12 .
Figure 2 The regulation of mesotrypsin expression in HaCaT cells is governed by a protein elimination system.
…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the samples was conducted using a TCS SPE system (Leica, Wetzlar, Germany). The primary antibodies utilized in this study included antibodies against β-actin (Sigma‒Aldrich), TGase-1 (Proteintech, Rosemont, USA), E-cadherin (ECCD2, a gift from Dr. Takeichi), LaminA/C (Cell Signaling, Danvers, USA), Lamin B1 (Abcam, Cambridge, UK), Rb, phosphorylated Rb (Cell Signaling Technology, Danvers, USA), ZO-1 (a gift from Dr. Nagafuchi), T7-tag (MBL, Tokyo, Japan), Ki67 (Abcam), Pro-FLG 12 , and GFP/Venus (culture supernatant of JFP-J1 cells, Riken Cell Bank RCB2309). Secondary antibodies conjugated to Alexa488, Cy3, or horseradish peroxidase (HRP) were obtained from Sigma‒Aldrich and Merck-Millipore (Darmstadt, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations